Ethnobotanical Study and Phytochemical Profiling of Traditionally Used Medicinal Plants of Georgia and Armenia: Symphytum caucasicum M. Bieb. (Boraginaceae) and Cyclamen coum Mill. (Primulaceae) - Mittova, Valentina; Roviello, Giovanni N.; Siradze, Marine; Gogoladze, Ana; Bidzinashvili, Roza; Gorgoshidze, Ekaterine; Makalatia, Khatuna; Loladze, Alexander; Tsaturyan, Avetis; Simonyan, Hayarpi; Sargsyan, Tatevik; Tseskhladze, Zurab R.; et al. (Modern Issues of Medicine and Management, 2025)
A variety of climate zones and unique relief make the Caucasus a hotspot, characterized by the highest biological diversity of any area with temperate forests worldwide. The Caucasus hotspot shelters 6350 species of vascular plants, at least 25% of which are unique to the region. For centuries, many Caucasian plants have been used in traditional medicine. Interestingly, in different countries, the same plant could have different applications in traditional medicine. In this study, we considered botanical characteristics, distribution, biochemical composition and use in traditional medicine of Symphytum caucasicum M. Bieb. and Cyclamen coum Mill., medicinal plants used in the traditional medicine of Armenia and Georgia. The review demonstrates that Caucasian medicinal plants Symphytum caucasicum M. Bieb. and Cyclamen coum Mill. are an important source of alkaloids, saponins and phenolic compounds. The review demonstrates the benefits of using Symphytum caucasicum M. Bieb. and Cyclamen coum Mill. for the treatment of different disorders, indicates different applications of these plants in traditional Armenian and Georgian medicine and offers information to produce safe plant-based medications.